P2 Pneumococcal conjugate vaccine failure in children younger than 5 years old in England and Wales, 2006–14. (27th April 2016) - Oligbu, GI; Collins, S; Andrews, N; Sheppard, C; Fry, N; Slack, M; Barrow, R; Ladhani, S
Abstract : Introduction and aims: The 7-valent (PCV7) and 13-valent (PCV13) pneumococcal conjugate vaccines (PCVs) are highly effective in preventing invasive pneumococcal disease (IPD) caused by vaccine serotypes and vaccine failure (vaccine-type IPD after age-appropriate immunisation) is rare. Although a number of studies have described children with PCV7 failure, little is known about PCV13 failure. Here, we describe the vaccination status, serotype distribution, risk factors, clinical characteristics and outcomes of children younger than 5 years with PCV7 and PCV13 failure over an eight-year period. Methods: Public Health England conducts enhanced surveillance for IPD and provides a national reference service for serotyping pneumococcal isolates in England and Wales. General practitioners are routinely contacted to complete surveillance questionnaires for children aged <5 years with laboratory-confirmed IPD. Results: A total of 163 episodes of PCV failure were confirmed in 161 children aged <5 years over eight years (During 04 September 2006 to 03 September 2014) in ten birth cohorts (04 September 2004 to 03 September 2014), with an overall vaccine failure rate of 0.82 (0.70–0.96) per 100, 000 vaccinated person-years. Of the 161 children, one third (n = 56, 35%) were exclusively PCV7 failures and 105 (65%) had received 1 PCV13 dose. Children with PCV13 failure were more likely to be healthy (87/105 [83%] vs. 37/56 [66%]; P = 0.016), present with lower respiratory tract infection (61/105 [58%] vs. 11/56 [20%]; P < 0.001) and develop empyema (41/61 [67%] vs. 1/11 [9%]; P < 0.001) compared to PCV7 failures. Children with co-morbidity were likely to be older (median age, 80.9 (IQR, 58.7–100.5) vs. 66.3 (48.8–83.4); P = 0.018) and present with septicaemia (P < 0.001). The case fatality rate was 3.1% (n = 5); four children had underlying co-morbidity (4/37 [10.8%] vs. 1/123 [0.81%); P = 002). Conclusions: PCV failure is rare in young children and, compared to PCV7 serotypes, the additional PCV13 serotypes are more likely to cause LRTI and empyema in healthy vaccinated children, but most children recover without sequelae. Given that most IPD cases in countries with established PCV13 programmes are currently due to non-PCV13 serotypes, there is an urgent need for serotype-independent subunit or whole-cell vaccines to control this devastating disease.